If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + 7 + -3x = -2 Reorder the terms: 7 + -6x + -3x = -2 Combine like terms: -6x + -3x = -9x 7 + -9x = -2 Solving 7 + -9x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -9x = -2 + -7 Combine like terms: 7 + -7 = 0 0 + -9x = -2 + -7 -9x = -2 + -7 Combine like terms: -2 + -7 = -9 -9x = -9 Divide each side by '-9'. x = 1 Simplifying x = 1
| 3xX+5=20 | | 4p-2p=20 | | 4(2x-13)+3x=58 | | 5(w-5)-7w=-27 | | 3(4u-2)=-30 | | 3x+18=2x-2 | | f^2-19=-1 | | 4x^5-2x^4+30x^3-15x^2+50x-25=f(x) | | 4(x-2)+2x=28 | | -25=5(2a-1)+2a | | 2(x+5)+(x-3)=16 | | 37+6x=9x-4 | | 17=16a+1 | | -5(5-x)=20 | | 4x-19x=30 | | (16x+14)-9x= | | 1x+8+9x=74-1x | | 3z-2=4 | | -4(-2x+2)=72 | | X/0.8=6 | | 4x-2(x-5)=-9+4x+13 | | 9+2(x-3)=45 | | 4x-2=4x-4+2 | | 8x-4=4x+19 | | -7(8+5x)=-266 | | 6p-9=2p+15 | | p(x)=x^4-8x^3+7x^2 | | 6y-4=y+5 | | F(x)=3(x-7)+12 | | 3x+7y=4fory | | 4x^3-2x^2+5x+1=0 | | -2t+15=3 |